Genotypic and phenotypic profiles of antibiotic‐resistant bacteria isolated from hospitalised patients in Bangladesh. Issue 7 (2nd May 2021) - Sarjana Safain, Kazi; Bhuyan, Golam Sarower; Hassan Hasib, Saad; Islam, Mohammad Sazzadul; Mahmud‐Un‐Nabi, Mohammad Al; Sultana, Rosy; Tasnim, Sadia; Noor, Farjana Akther; Sarker, Suprovath Kumar; Islam, Md Tarikul; Rahat, Asifuzzaman; Leung, Daniel T.; et al.
Abstract: Objectives: Characterisation of resistance phenotype and genotype is crucial to understanding the burden and transmission of antimicrobial resistance (AMR). This study aims to determine the spectrum of AMR and associated genes encoding aminoglycoside, macrolide and β‐lactam classes of antimicrobials in bacteria isolated from hospitalised patients in Bangladesh. Methods: 430 bacterial isolates from patients with respiratory, intestinal, wound infections and typhoid fever, presenting to clinical care from 2015 to 2019, were examined. They included Escherichia coli ( n = 85); Staphylococcus aureus ( n = 84); Salmonella typhi ( n = 82); Klebsiella pneumoniae ( n = 42); Streptococcus pneumoniae ( n = 36); coagulase‐negative staphylococci ( n = 28); Enterococcus faecalis ( n = 27); Pseudomonas aeruginosa ( n = 26); and Acinetobacter baumannii ( n = 20). Reconfirmation of these clinical isolates and antimicrobial susceptibility tests was performed. PCR amplification using resistance gene‐specific primers was done, and the amplified products were confirmed by Sanger sequencing. Results: 53% of isolates were multidrug‐resistant (MDR), including 97% of Escherichia coli . There was a year‐wise gradual increase in MDR isolates from 2015 to 2018, and there was an almost twofold increase in the number of MDR strains isolated in 2019 ( P = 0.00058). Among the 5 extended‐spectrum β‐lactamases investigated, CTX‐M‐1 was the most prevalent (63%) followed by NDM‐1 (22%); Escherichia coli was the major reservoir of these genes. The ermB (55%) and aac(6′)‐Ib (35%) genes were the most frequently detected macrolide and aminoglycoside resistance genes, respectively. Conclusion: MDR pathogens are highly prevalent in hospital settings of Bangladesh.